ANALISIS STRUKTUR PEREKONOMIAN DAN PERTUMBUHAN EKONOMI DI KOTA MANADO (Economic Structure and Economic Growth Analysis in Manado City) - Ira Yuliana Posumah; Theodora Katiandagho; Meisye Jellie Memah (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the structure of the economy, the contribution of each economic category, and potential business sectors in Manado City. This study used a quantitative descriptive approach by collecting secondary data of Gross Regional Domestic Product and Economic Growth Rate from the Central Bureau of Statistics, Manado City. Data processing was conducted by analyzing the contribution of the business field category, Shift Share, Location Quotient, and Dynamic Location Quotient, using the Microsoft Excel 2016 application.The results showed that the categories of wholesale and retail trade, car and motorcycle repairs consistently provided the largest contribution to the Gross Regional Domestic Product of Manado City in the period from 2013 to 2019. Based on the analysis results of Location Quotient and Dynamic Location Quotient, the categories of:Â  wholesale and retail; car and motorcycle repair; transportation and warehousing; provision of accommodation and food and drink; information and communication; financial and insurance services; corporate services; government administration; defense, and compulsory social security; education service; health services and social activities; and other services were found to be base or superior categories to the economic structure of Manado City. In the shift share calculation method, the real impact of growth (Dij) from 2013 to 2019 provided changes or developments to the regional economic structure of Manado City. The sectorial GRDP of Manado City had grown by Rp. 29,765,900,000,000.